2019
DOI: 10.1016/j.neuroimage.2018.10.029
|View full text |Cite
|
Sign up to set email alerts
|

Limits to anatomical accuracy of diffusion tractography using modern approaches

Abstract: Diffusion MRI fiber tractography is widely used to probe the structural connectivity of the brain, with a range of applications in both clinical and basic neuroscience. Despite widespread use, tractography has well-known pitfalls that limits the anatomical accuracy of this technique. Numerous modern methods have been developed to address these shortcomings through advances in acquisition, modeling, and computation. To test whether these advances improve tractography accuracy, we organized the 3-D Validation of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
113
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 217 publications
(114 citation statements)
references
References 59 publications
1
113
0
Order By: Relevance
“…It is important to point out that we are not suggesting the use of no thresholds for tractography, as it actually causes a distinct loss of specificity, and only use this as an example to show that removing this threshold results in similar tracts for all tested response functions. In fact, no algorithmic parameters have both high specificity and sensitivity, in agreement with tractography validation studies, [49][50][51] and in practice it is important to have some threshold to control the number of false positive bundles. While different choices of tracking parameters can produce large variations, it is important to point out that, with typical usage (ie typical parameters), different response functions also lead to different tractography results.…”
Section: Discussionmentioning
confidence: 68%
“…It is important to point out that we are not suggesting the use of no thresholds for tractography, as it actually causes a distinct loss of specificity, and only use this as an example to show that removing this threshold results in similar tracts for all tested response functions. In fact, no algorithmic parameters have both high specificity and sensitivity, in agreement with tractography validation studies, [49][50][51] and in practice it is important to have some threshold to control the number of false positive bundles. While different choices of tracking parameters can produce large variations, it is important to point out that, with typical usage (ie typical parameters), different response functions also lead to different tractography results.…”
Section: Discussionmentioning
confidence: 68%
“…Finally, tractography algorithms with their ability to delineate eloquent fiber tracts has important clinical implications for the surgical treatment of malignant brain tumors [33]. Although no current method solves the inherent limitations of fiber tractography, the techniques available are sufficiently specific and sensitive to make fiber tractography a valuable tool for the neurosurgeon [34,35]. However, the standard tensor fit does not account for any free water compartment, and in the presence of significant partial voluming of extracellular fluid, indices derived from the fitted tensor represent erroneous estimations of the underlying tissue, including low FA.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of retrograde tracing, histological tracing also quantifies the number of axons in a projection, since each labeled projection neuron provides one axon. Studies performed in macaque (Azadbakht et al, 2015;Donahue et al, 2016;Schilling, Nath, et al, 2019;Zhang et al, 2018) , squirrel monkey (Gao et al, 2013; , pig (Knösche, Anwander, Liptrot, & Dyrby, 2015) , mouse (Calabrese, Badea, Cofer, Qi, & Johnson, 2015) and rat (Sinke et al, 2018) , have explored the relationship between tract-tracing experiments and tractography. Overall these studies have shown that diffusion MRI tractography provides a good estimate of structural brain connectivity.…”
Section: Introductionmentioning
confidence: 99%